Electromyography analysis during lifting tasks: a pilot study - Ahmad, Siti Anom; Kamarudin, Nor Hafeezah; Mohd Yusuff, Rosnah; Hassan, Mohd Khair; Md. Dawal, Siti Zawiah (Universiti Putra Malaysia Press, 2017)
Manual Material Handling (MMH) involves lifting, bending, and twisting motions of the torso. Poor lifting technique is often considered a major risk factor in low back injury associated with manual lifting tasks. Currently, there is little work on the effects of lifting on the Malaysian population. The MMH activities that was designed with the different lifting heights, frequency, weight of loads and the effect on of biceps and triceps muscle contraction of the subjects during the lifting tasks were studied. The parameters involved are weight of the loads lifted, height of the loads lifted and lifting frequency as the independent variables. Whereas the dependent variable is Electromyography (EMG) signal. The weight loads are varying from 10kg up to 24kg and the heights of the loads travels from the floor to 70cm and 130cm heights. The frequency of lifting is set to 1 lift and 6 lifts per minute. 14 healthy male and female subjects were recruited in this study. The questionnaires and consent form were used to identify the health condition of the subjects before performing the lifting tasks. The EMG activity was recorded and collected from biceps and triceps muscles using the Shimmer EMG system. This method is used in determining the maximum acceptable weight limit (MAWL) that can be lifted by the subjects in the lifting tasks. This research aims to design a lifting equation that suits for Malaysian people. Therefore, the effects of different manual lifting tasks on Malaysian physiological limits need to be identified.